2011
DOI: 10.1089/ars.2010.3378
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor for Advanced Glycation End-Products (RAGE) Protects Pancreatic Tumor Cells Against Oxidative Injury

Abstract: Reactive oxygen species, including hydrogen peroxide (H 2 O 2 ), can cause toxicity and act as signaling molecules in various pathways regulating both cell survival and cell death. However, the sequence of events between the oxidative insult and cell damage remains unclear. In the current study, we investigated the effect of oxidative stress on activation of the Receptor for Advanced Glycation End-products (RAGE) and subsequent protection against H 2 O 2 -induced pancreatic tumor cell damage. We found that exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 50 publications
2
70
0
Order By: Relevance
“…2A). Consistent with our previous observations in vitro (6,7), targeted ablation of RAGE decreased levels of autophagy [microtubule-associated protein light chain 3 (LC3)] in PanIN lesions ( Fig. 2B and Fig.…”
Section: Rage Promotes Development Of Panin Lesions In the Setting Ofsupporting
confidence: 92%
See 4 more Smart Citations
“…2A). Consistent with our previous observations in vitro (6,7), targeted ablation of RAGE decreased levels of autophagy [microtubule-associated protein light chain 3 (LC3)] in PanIN lesions ( Fig. 2B and Fig.…”
Section: Rage Promotes Development Of Panin Lesions In the Setting Ofsupporting
confidence: 92%
“…Our previous studies have demonstrated that RAGE is a positive regulator of autophagy during chemotherapy and oxidative stress (6,7). Consistent with these observations, we found that knockdown of RAGE in pancreatic cancer cells decreased IL-6 and STAT3 cDNA-induced conversion of LC3-I to LC3-II (Fig.…”
Section: Autophagy Regulates Mitochondrial Localization and Function Ofsupporting
confidence: 89%
See 3 more Smart Citations